ANALISIS KEBIJAKAN DESA SIAGA DI KABUPATEN SLEMAN YOGYAKARTA - Kusuma, Reni Merta (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: Mortality rate is one of indicators andrepresentations of welfare of an area. In order to solve highmortality rate problem, the government of Daerah IstimewaYogyakarta (DIY), including District of Sleman, is carrying outthe policy of alert village.Method: The study used literature review based onreferences and field data which were issued by Health Office.Result: The policy of alert village has less positive impact indecreasing maternal mortality rate and neonatal mortality rate,because health assurance scheme still does not meet theneeds of the people, both physical and non-physical. Thedegree of health still has not improved significantly. The policyof alert village needs inter-sectoral financial support. Financialallocation is still mistargeting. People needs vary from onevillage to another, so it is necessary to have competent andsmart health workers as the implementing agents of HealthDepartment. The policy of alert village is still not able to satisfyall stakeholders (government, health workers, and people),because the concept of satisfaction is closely related to theprinciple of justice.Conclusion: The policy of alert village is an effort to empowerthe people to be independent in overcoming their healthproblems. But, in District of Sleman the policy of alert village isclassified into unsuccessfull policy. This failure is caused byinsufficiet support in implementating the policy.Keyword: Policy of alert village, Health Office of District Sleman